Influence of extensional strike-slip fault systems on hydrocarbon accumulation: case studies from Huanghekoudong and Miaoxi’nan sub-sags - Fu, Sheng; Wang, Deyu; Yang, Haifeng; Song, Lijun; Ma, Ming; Wang, Kaiyu (Frontiers in Earth Science, 2024)
Extensional strike-slip basins have unique structural features that influence both sub-sags and traps. Despite previous investigations into the extension-strike-slip fault system, there remains a gap in the comprehensive analysis of its influence on sub-sag formation and trap development. The Huanghekoudong and Miaoxi’nan sub-sags within the Bohai Bay Basin, intersected by the Tan-Lu Fault Zone, offer exemplary cases for examining the interplay between strike-slip and extensional tectonic regimes. The neotectonic strike-slip movements along the Tan-Lu Fault Zone have given rise to various extensional strike-slip overlap zones in these sub-sags, rendering these locales ideal for investigating the dynamics of strike-slip and extensional tectonic processes. Employing three-dimensional seismic data, well logs, and a newly constructed sequence stratigraphic framework, our research delineates the geometric and kinematic phenomena characteristic of the extensional strike-slip fault system, including the dynamics of extensional fault deformation and interaction through time. By scrutinizing the fault system’s vital role in shaping sub-sag evolution and trap genesis, we present a comprehensive model that significantly contributes to our understanding of structural trapping dynamics. This model not only fine-tunes existing trapping models but also offers invaluable insights for future exploration strategies within the Bohai Bay Basin and other similar extensional strike-slip basins worldwide. Our findings highlight the novel and significant implications of the extensional strike-slip fault system in controlling sub-sag and trap features, thus bridging a notable gap in existing geotechnical knowledge.